2015
DOI: 10.3109/00498254.2015.1070975
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of artemisinin–chloroquinoline hybrids for potential metabolic liabilities

Abstract: 1. Chemotherapy remains the effective way of controlling malaria infections. Many of the treatments have been rendered ineffective as a result of drug resistance by plasmodia species as well as toxicity. Molecular hybridisation is one of the techniques used in the synthesis of new-generation antimalarial techniques. In this paper, we explore some potential metabolic challenges associated with this technique. 2. In vitro metabolic clearance and metabolite identification were performed in cryopreserved hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Moreover, artesunate showed a low clearance rate. In the literature, artesunate is categorized as a drug of low to intermediate hepatic clearance [49, 50]. Among the compounds, artesunate showed the lowest clearance (Cl int of 11.6 µL/min/mg of protein) and hybrid 2 the highest (Cl int between 186.88 and 422.86 µL/min/mg of protein).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, artesunate showed a low clearance rate. In the literature, artesunate is categorized as a drug of low to intermediate hepatic clearance [49, 50]. Among the compounds, artesunate showed the lowest clearance (Cl int of 11.6 µL/min/mg of protein) and hybrid 2 the highest (Cl int between 186.88 and 422.86 µL/min/mg of protein).…”
Section: Resultsmentioning
confidence: 99%
“…Thelingwani et al (83) addressed the various metabolic challenges that arise in covalently linking two active pharmacophores by characterizing artemisinin-chloroquinoline hybrids (47) and concluded that though the technique combines the desirable properties, certain unfavorable properties are also carried along in the process and need to be accounted for. The experiment investigating metabolic stability and metabolite identification showed that the hybrids were not extensively metabolized, with the major amount of the parent compound remaining unchanged after 1 h of incubation in hepatocytes.…”
Section: New Metabolic Liabilities That Arise By Molecular Hybridizationmentioning
confidence: 99%